The macroeconomic impact of COVID-19 in EMEs - Marco Hernandez-Vega (Banco de México, 2024)
The COVID-19 pandemic caused severe losses in the world economy, particularly in emerging market economies (EMEs), which had to withstand the challenges of the pandemic and its domestic repercussions while also facing the deterioration of external demand. Using a panel data model, we estimate how the number of deaths and lockdown measures affected GDP growth, the unemployment rate, and export growth from January 2020 to September 2021, based on a sample of 25 countries grouped into three regions. The results indicate that lockdown measures had a negative and statistically significant impact on GDP growth across all regions, with some variation in the size of the estimated coefficients. Consequently, Latin America was the region most sensitive to these measures, followed by Asia and the Middle East.
Keywords: C01; E01; I00; 330; COVID-19; Economic Impact; Growth; Lockdown Policies